Generative AI Readiness dan Innovative Work Behavior: Peran Mediasi Learning Agility Karyawan - Sunarto Sunarto; Mey Ratu Vilanita; Nabila Farah Davina; Misel Thomas Sarira; Tassia (Indo-MathEdu Intellectuals Journal, 2026)
This research is motivated by the unclear extent to which employee readiness to face Generative AI influences innovative work behavior, as well as the role of Learning Agility in strengthening this relationship. This study aims to examine the effect of Generative AI Readiness on Innovative Work Behavior with Learning Agility as a mediating variable. The study used a quantitative approach through a survey of employees from various organizational sectors that have adopted or are preparing to implement AI technology. Data were collected using a structured questionnaire and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results showed that Generative AI Readiness has a positive and significant effect on Learning Agility and Innovative Work Behavior. In addition, Learning Agility also has a positive effect on Innovative Work Behavior and is proven to significantly mediate the relationship between Generative AI Readiness and Innovative Work Behavior. These findings indicate that employee readiness in facing Generative AI not only has a direct impact on innovative work behavior but also strengthens learning and adaptation abilities that drive innovation. This research provides theoretical contributions to the study of technology-based organizational behavior as well as practical implications for organizations in developing digital competencies and employee learning.